Vibrio cholerae ToxR Downregulates Virulence Factor Production in Response to Cyclo(Phe-Pro) - X. Renee Bina (American Society for Microbiology, 2013)
ABSTRACT Vibrio cholerae is an aquatic organism that causes the severe acute diarrheal disease cholera. The ability of V. cholerae to cause disease is dependent upon the production of two critical virulence determinants, cholera toxin (CT) and the toxin-coregulated pilus (TCP). The expression of the genes that encode for CT and TCP production is under the control of a hierarchical regulatory system called the ToxR regulon, which functions to activate virulence gene expression in response to in vivo stimuli. Cyclic dipeptides have been found to be produced by numerous bacteria, yet their biological function remains unknown. V. cholerae has been shown to produce cyclo(Phe-Pro). Previous studies in our laboratory demonstrated that cyclo(Phe-Pro) inhibited V. cholerae virulence factor production. For this study, we report on the mechanism by which cyclo(Phe-Pro) inhibited virulence factor production. We have demonstrated that exogenous cyclo(Phe-Pro) activated the expression of leuO, a LysR-family regulator that had not been previously associated with V. cholerae virulence. Increased leuO expression repressed aphA transcription, which resulted in downregulation of the ToxR regulon and attenuated CT and TCP production. The cyclo(Phe-Pro)-dependent induction of leuO expression was found to be dependent upon the virulence regulator ToxR. Cyclo(Phe-Pro) did not affect toxR transcription or ToxR protein levels but appeared to enhance the ToxR-dependent transcription of leuO. These results have identified leuO as a new component of the ToxR regulon and demonstrate for the first time that ToxR is capable of downregulating virulence gene expression in response to an environmental cue. IMPORTANCE The ToxR regulon has been a focus of cholera research for more than three decades. During this time, a model has emerged wherein ToxR functions to activate the expression of Vibrio cholerae virulence factors upon host entry. V. cholerae and other enteric bacteria produce cyclo(Phe-Pro), a cyclic dipeptide that we identified as an inhibitor of V. cholerae virulence factor production. This finding suggested that cyclo(Phe-Pro) was a negative effector of virulence factor production and represented a molecule that could potentially be exploited for therapeutic development. In this work, we investigated the mechanism by which cyclo(Phe-Pro) inhibited virulence factor production. We found that cyclo(Phe-Pro) signaled through ToxR to activate the expression of leuO, a new virulence regulator that functioned to repress virulence factor production. Our results have identified a new arm of the ToxR regulon and suggest that ToxR may play a broader role in pathogenesis than previously known.